The Association of E-Cigarettes with Hypogonadism in Adult Men in Denpasar - Djuanda, Louis Felix; I Gusti Ngurah Pramesemara; I Made Oka Negara; Jaqueline Sudiman; Faisal Yusuf Azhari (Universitas Airlangga, 2024)
Background : A decrease in testosterone level can cause a set of symptoms forming a clinical syndrome called hypogonadism. One of the factors that is known to disrupt testosterone levels is smoking habits. Currently, the use of e-cigarettes as an alternative product to conventional cigarettes is increasing rapidly in many countries, including Indonesia. The amounts of harmful substances in e-cigarette aerosols are similar to the smoke produced by conventional cigarettes, but the health hazards of e-cigarettes are still not well known. Objective : This study was conducted to determine the relationship between e-cigarettes and hypogonadism in adult men in the city of Denpasar. Method: This study uses a descriptive-analytical method in the form of a cross-sectional study. The research sample consisted of 49 e-cigarette users collected using consecutive sampling techniques. The data were then analyzed using SPSS® version 26. Results : Based on the research obtained from the ADAM score from a total of 49 samples, the prevalence of hypogonadism is higher in the group of people who smoked e-cigarettes, about 35,3%. Overall, this study found a fairly high prevalence of hypogonadism (26.5%) in Denpasar. The chi-square test shows a p-value of 0,032 and a prevalence ratio (PR) of 5.294. Conclusions : Active use of e-cigarettes showed a significant association with the incidence of hypogonadism experienced by adult men in Denpasar. Based on the PR calculation, the risk of hypogonadism in active e-cigarette users was 5.294 times higher than that of adult men who were not active e-cigarette users.